A distribution dynamics approach to regional income convergence in reunified Germany - Falko Juessen (European Regional Science Association (ERSA), 2005)
In this paper, we present an empirical study of per capita income convergence across German labour market regions during 1992 to 2002 using nonparametric techniques. We find clear evidence for convergence during the period we study, i.e. that regions that were poor in 1992 have increased their relative incomes in 2002. A special feature of our approach is that it allows to make predictions about the long-run distribution of regional incomes. We predict a persistent inequality among German regions. This result is especially important with respect to the massive regional policy expenditures taken in the last decade. According to our analysis it is unlikely that German policy will prevent polarization in the regional income distribution even if transers and subsidies will be continued in a comparable magnitude. Consequently, we argue that regional policy programs in Germany do not achieve their aim, and therefore need to be reviewed.
Keywords: 330